2016
DOI: 10.1177/0033294115626640
|View full text |Cite
|
Sign up to set email alerts
|

Self-Rated ADHD Symptoms Among Biological Mothers or Fathers of Children with Confirmed ADHD in a French Population

Abstract: Parents of children with ADHD are more likely to present the disorder, which can affect quality of life and parenting strategies. Few studies have examined parental ADHD to date, none in France. Prevalence of self-rated ADHD symptoms in adulthood and childhood was estimated among 60 biological mothers or fathers of children with confirmed ADHD in France. Cutoffs were total score ≥46 on the Wender Utah Rating Scale and ≥4 on the Adult ADHD Self-Report Scale Screener. Results indicated possible child and adult A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0
3

Year Published

2017
2017
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 40 publications
0
6
0
3
Order By: Relevance
“…The flowchart in Figure 1 illustrates the process of screening and data extraction undertaken in the review. Overall, 18 studies [32][33][34][35][36][37][38][39][40][41][42][43][44][45][46][47][48][49] were identified to have reported on the prevalence of mental illness among parents of children receiving treatment in CAMHS.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…The flowchart in Figure 1 illustrates the process of screening and data extraction undertaken in the review. Overall, 18 studies [32][33][34][35][36][37][38][39][40][41][42][43][44][45][46][47][48][49] were identified to have reported on the prevalence of mental illness among parents of children receiving treatment in CAMHS.…”
Section: Resultsmentioning
confidence: 99%
“…Other studies had a focus on prevalence rates in relation to specific mental illnesses, either in the parent [40] (see Table 4) or the child [41][42][43] (see Table 5). Finally, some studies reported the number of parents with a specific mental illness who had children attending CAMHS with a specific mental illness [44][45][46][47][48][49] (see Table 6).…”
Section: Reported Prevalence Of Mental Illness Among Parents Of Children Attending Camhsmentioning
confidence: 99%
See 2 more Smart Citations
“…The heritability of ADHD is high [7] and many children with ADHD have parents who show ADHD symptoms themselves [8, 9]. Furthermore, parents with ADHD are more likely to have deficits in parenting than parents without ADHD [1012].…”
Section: Introductionmentioning
confidence: 99%